5PSQ-095 Analysis of the toxicities associated with tyrosine kinase inhibitors in patients with chronic myeloid leukaemia. (24th March 2020) - Garreta, G; Manzaneque, A; Velez, P; Giralt, M; Castells, G; Arcenillas, P; Meca, N; Sebastian, C; Nicolas, J
Abstract : Background and importance: Pharmacological toxicity management of tyrosine kinase inhibitor (TKI) use is important in the setting of chronic use in chronic myeloid leukaemia (CML) patients. Aim and objectives: The aim of this study was to describe TKI toxicity in patients diagnosed with CML. Material and methods: This was a retrospective study of patients with CML treated in our hospital with TKIs from June 2010 to July 2019. We collected data on TKIs prescribed, treatment line, toxicities (haematological (TH)/non-haematological (NHT)) according to CTCAE V.5 and time of occurrence, demographic data, Charlson index, Sokal index, concomitant medication, molecular response and dose modifications/discontinuations. Results: A total of 37 patients (19/37 women, median age 59 years (33–89)) were included. The median Charlson index was 2 (0–8). The Sokal index at diagnosis (23/37) was: low (14), medium (6) and high (3). Patients had a median of 4 (0–12) drug prescriptions. At the time of data analysis, the pattern of TKI prescriptions was: imatinib (23/37), dasatinib (4/37) and nilotinib (3/37) as firstline treatment; and imatinib (4/37), dasatinib (12/37), nilotinib (4/37), bosutinib (2/37) and ponatinib (1/37) as second or subsequent lines of treatment. When the data were collected, 18 patients achieved a deep molecular response (12/37 imatinib and 3/37 nilotinib). Median toxicity/patient was 3 (1–13), appearing in an average time of 18 months (28 days–8 years) and 10 months (8 days–7 years) for TH (23/122) and NHT (99/122), respectively. Dose was reduced because of toxicity in 7/37 patients and was discontinued in 14/37. Conclusion and relevance: The analysis has allowed the implementation of a specific proactive follow-up for each drug, which means early recognition and management of the toxicities associated with TKIs to optimise treatment efficacy and safety, as well as patient quality of life. References and/or acknowledgements: No conflict of interest.